Leveraging Scaled Agile Framework to Develop Information Systems in Finance Field - Alotaibi, Dinah Dhaif Allah; Alrwais, Omer (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This research investigates the application of the Scaled Agile Framework (SAFe) in Saudi financial institutions, focusing on its impact on scalability, regulatory compliance, security, and speed in system development. The study aims to explore the benefits and challenges of SAFe adoption in a highly regulated and hierarchical industry. Data was collected from six articles, employing a qualitative analysis to examine how SAFe addresses the critical needs of financial organizations in adapting to dynamic market conditions while ensuring compliance with strict regulations. The findings reveal that SAFe enhances scalability by improving team collaboration and governance processes, which is crucial for large financial institutions. Additionally, its iterative approach facilitates ongoing regulatory compliance and allows rapid adaptation to regulatory changes. The integration of security protocols into the continuous development process helps reduce vulnerabilities, while the structured nature of SAFe accelerates product delivery, improving responsiveness to market demands. Despite these advantages, challenges include limited experience with large-scale Agile frameworks, balancing compliance with agility, and resistance to organizational change. The study highlights the need for further research, particularly primary data collection from Saudi financial institutions, to better understand the local challenges and opportunities for SAFe adoption in this rapidly evolving industry.